2016
DOI: 10.1002/2015jg003125
|View full text |Cite
|
Sign up to set email alerts
|

Changes to freshwater systems affecting Arctic infrastructure and natural resources

Abstract: The resources component of the Arctic Freshwater Synthesis focuses on the potential impact of future climate and change on water resources in the Arctic and how Arctic infrastructure and exploration and production of natural resources are affected. Freshwater availability may increase in the Arctic in the future in response to an increase in middle-and high-latitude annual precipitation. Changes in type of precipitation, its seasonal distribution, timing, and rate of snowmelt represent a challenge to municipal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 33 publications
0
84
0
Order By: Relevance
“…Although the final effects on freshwater supply and distribution in the Arctic Freshwater System due to changes in storm tracks or enhanced moisture from ice‐free freshwater ponds/lakes/rivers and an ice‐diminished Arctic Ocean need to be determined, the higher‐latitude terrestrial areas of the AFD are generally becoming more “water rich” (i.e., where water availability meets or exceeds the needs of human development and ecosystem services) [ Bring et al , ; Lique et al , ], particularly during winter when, in response to warming, increases in precipitation exceed that for evaporation [ Vihma et al , ]. Based on the review by Instanes et al [], this is likely to translate into an economic benefit via the additional hydropower generation capacity it creates, especially when augmented by other freshwater sources, such as from enhanced glacier melt (e.g., as already initiated in Greenland). While large‐scale hydropower facilities are located only in currently strategic watersheds, it is possible that an expansion of such facilities might occur with an increase in the flow of northern rivers, particularly if energy demands at high latitudes also increases.…”
Section: Key Emerging Issues and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the final effects on freshwater supply and distribution in the Arctic Freshwater System due to changes in storm tracks or enhanced moisture from ice‐free freshwater ponds/lakes/rivers and an ice‐diminished Arctic Ocean need to be determined, the higher‐latitude terrestrial areas of the AFD are generally becoming more “water rich” (i.e., where water availability meets or exceeds the needs of human development and ecosystem services) [ Bring et al , ; Lique et al , ], particularly during winter when, in response to warming, increases in precipitation exceed that for evaporation [ Vihma et al , ]. Based on the review by Instanes et al [], this is likely to translate into an economic benefit via the additional hydropower generation capacity it creates, especially when augmented by other freshwater sources, such as from enhanced glacier melt (e.g., as already initiated in Greenland). While large‐scale hydropower facilities are located only in currently strategic watersheds, it is possible that an expansion of such facilities might occur with an increase in the flow of northern rivers, particularly if energy demands at high latitudes also increases.…”
Section: Key Emerging Issues and Future Researchmentioning
confidence: 99%
“…The objectives of this AFS summary article are to review key emerging issues of the AFS, especially those that are cross-thematic in nature, and to identify related future research directions to address such issues. More details about knowledge gaps and proposed future research are contained within the individual thematic articles, which include atmosphere [Vihma et al, 2016], oceans [Carmack et al, 2016], terrestrial hydrology [Bring et al, 2016], terrestrial ecology [Wrona et al, 2016], resources [Instanes et al, 2016], and modeling [Lique et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…The exact nature of long‐term effects on the climate system from changing river flows and associated freshwater cycling in the Arctic is far from understood, but evidence suggests that these effects will be substantial [ Rawlins et al ., ; Hinzman et al ., ; Bintanja and Selten , ; Haine et al ., ]. Notwithstanding unresolved couplings between components of the Arctic climate system [ Park et al ., , ; Carmack et al ., ; Lique et al ., ; Vihma et al ., ], changes to Arctic rivers will also strongly affect about 40 million people who reside in their combined drainage area [ Stephenson and Smith , ; Instanes et al ., ]. River flow influences such diverse processes and systems as transportation routes, ecosystem functioning, permafrost degradation patterns, mining and fossil fuel extraction, and spatial planning.…”
Section: Introductionmentioning
confidence: 99%
“…Derksen and Brown (2012) found that observed reductions in June snow cover extent since 2005 were far below model projections. Ultimately, the influence of future environmental change is likely to depend on local geography and socioeconomic factors, such as infrastructure and development (Instanes et al 2016). The nearterm vulnerability of Lake Geraldine and Lake Nipissar to climate anomalies and high consumption events illustrates the immediate need for a real-time monitoring program to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, during years of warm summers and cold winters, there may be pronounced vulnerability to diminished end-of-winter supply if reservoirs do not fully recharge prior to ice formation. The shallow nature of Arctic supply lakes leaves them more susceptible to the effects of lake ice and an overall lower rate of recharge (Instanes et al 2016). For example, Lake Nipissar has a maximum reported useable depth of only 4.6 m measured above the intake, with~56% of the accessible volume stored in ice at the end of the winter (Stantec Consulting Ltd. 2014).…”
Section: Supply Forecastsmentioning
confidence: 99%